Benefit Application of Knowledge Management for Lecturer Performance During the Covid 19 Pandemic - Wahyudi Wahyudi; Denok Sunarsi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Dynamics comes unexpectedly, like this Covid-19. Since the beginning of 2020, the pandemic has significantly changed the order of life, including higher education institutions. In conditions like this, the wisest attitude that can be taken is to adapt. This means that the institution maximizes the potential of knowledge management in order to present relevant work models and maintain the existence of performance. In fact, this study aims to reveal how knowledge management in its implementation can be one of the solutions in maintaining and maintaining lecturer performance during the pandemic. To answer this goal, a qualitative approach was established, in an effort to get a complete picture of the phenomenon raised. The determination of the unit of analysis is based on the criteria that have been established through purposive techniques, then in the discussion of the research results descriptive analysis is used. The results of the study can be illustrated, in general or more or less knowledge management helps the management of higher education institutions in adapting to the pandemic situation, especially in maintaining the performance of lecturers in carrying out education. This is evident, knowledge management encourages the birth of a technology-based online education system, so that the performance of lecturers in the field of education does not decline. Likewise in the field of research and service, knowledge management initiates the birth of a system-oriented adaptive work model. This means that even though the COVID-19 pandemic has created many limitations on activities, with the application of knowledge management, research and service activities will continue as usual. Of course, this situation confirms that knowledge management has great benefits for the existence of the performance of lecturers and institutions.